Quantifying the roles of food intake and stored lipid for growth and development throughout the life cycle of a high-latitude copepod, and consequences for ocean carbon sequestration - Anderson, Thomas R.; Hessen, Dag O.; Gentleman, Wendy C.; Yool, Andrew; Mayor, Daniel J. (Frontiers in Marine Science, 2022)
Copepods are a critical component of ocean ecosystems, providing an important link between phytoplankton and higher trophic levels as well as regulating biogeochemical cycles of carbon (C) and nutrients. Lipid-rich animals overwinter in deep waters where their respiration may sequester a similar quantity of C as that due to sinking detritus. This ‘seasonal lipid pump’ nevertheless remains absent from global biogeochemical models that are used to project future ocean-climate interactions. Here, we make an important step to resolving this omission by investigating the biogeochemical cycling of C and nitrogen (N) by high-latitude copepods using a new individual-based stoichiometric model that includes explicit representation of lipid reserves. Simulations are presented for Calanus finmarchicus throughout its life cycle at Station Mike (66°N, 2°E) in the Norwegian Sea, although the model is applicable to any suitable location and species with a similar life history. Results indicate that growth, development and egg production in surface waters are driven primarily by food intake (quantity) which provides a good stoichiometric match to metabolic requirements. In contrast, the main function of stored lipid is to support overwintering respiration and gonad development with these two processes respectively accounting for 19 and 55% of the lipid accumulated during the previous spring/summer. The animals also catabolise 41% of body protein in order to provide N for the maintenance of structural biomass. In total, each individual copepod sequesters 7.0 μmol C in deep water. If the areal density of animals is 15,000–40,000 m-2, these losses correspond to a sequestration of 1.7–4.6 g C m-2 yr-1. Lipids contributed only 1% of the C used in egg production in the following year. Accumulating extra lipid in spring would potentially increase egg production but our analysis suggests that any such benefit is outweighed by a higher risk of predator mortality. Our work indicates that the seasonal lipid pump may be of similar magnitude to C sequestration via sinking particles in the North Atlantic and highlights the need for improved physiological understanding of lipid use by high-latitude copepods in order to better constrain C fluxes in ocean food-webs and biogeochemical models.